2015
DOI: 10.1186/s13620-015-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rapid laboratory tests for failure of passive transfer in the bovine

Abstract: BackgroundFailure of passive transfer of maternal immunity via colostrum can occur in the bovine, and a number of blood tests have been developed to test calves for this failure. It is not clear which test is most suitable for this purpose. The objective was to examine the most commonly used tests for failure of passive transfer and to decide which is most suitable for routine laboratory use. 126 serum samples were taken from calves of dairy cows after birth but prior to colostrum feeding, and at 48 h of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 55 publications
4
46
1
3
Order By: Relevance
“…In this study, the ZST test had the lowest AUC for diagnosing http://FTPI. The majority of studies that evaluated the diagnostic performance of the ZST test for detecting FPTI found variable Se and Sp values for diagnosing FPTI . Our results were in agreement with the findings of most studies; we identified an Se = 100% and an Sp = 67% at an optimal cut point for the ZST test of <14.6 g/L for diagnosing FPTI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the ZST test had the lowest AUC for diagnosing http://FTPI. The majority of studies that evaluated the diagnostic performance of the ZST test for detecting FPTI found variable Se and Sp values for diagnosing FPTI . Our results were in agreement with the findings of most studies; we identified an Se = 100% and an Sp = 67% at an optimal cut point for the ZST test of <14.6 g/L for diagnosing FPTI.…”
Section: Discussionsupporting
confidence: 90%
“…A diagnostic test with a high Se should be selected as a screening test. Concerns have been expressed about the effect of temperature on the ZST reaction, the effect of CO 2 on the ZnSO 4 solution, and the effect of the degree of hemolysis in the serum samples, although modifications have been proposed to reduce errors due to hemolysis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of salts causes turbidity, which may be visually evaluated or measured using a spectrophotometer as units of turbidity. This method may be used as a field test for the evaluation of suckling efficiency or failure of passive transfer of maternal immunity via colostrum in calves and foals (Sedlinska et al 2005;Hogan et al 2015). Currently, the bromcresol green (BCG) and bromcresol purple methods are the basis for the determination of serum albumin (Watanabe et al 2004).…”
Section: Albumin and Globulinsmentioning
confidence: 99%
“…Protection from infectious diseases of newborn calves is completely dependent on the success of passive transfer of maternal IgG via the colostrum [2]. Because of that, failure of passive transfer (FPT) of colostral immunoglobulins, composed mainly of IgG [2], is associated with increased morbidity and mortality [2][3][4][5][6][7][8][9][10][11]. FPT of immunoglobulins is defi ned as a circulating IgG concentration less than 10 g/L in newborn calves between 24 and 48 hours of age [12,13].…”
Section: Introductionmentioning
confidence: 99%